HERMENEUTIKA HEIDEGGER DAN RELEVANSINYA TERHADAP KAJIAN AL-QUR’AN - Arif, Muhammad (Jurnal Studi Ilmu-ilmu Al-Qur'an dan Hadis, 2015)
ange-newline"> </The integration of hermeneutics and the study of Qur’anic interpretation is still considered as a taboo. This article reviewes the hermeneutic conception of Heidegger’s Dasein and looks for its relevance to the study of Qur’anic interpretation. Theories within Heidegger’s Dasein that can be used tostrengthen Qur’anic studies are theory of facticity, temporality, and theontological-existential. In the midst of the development of contemporarysciences such as hermeneutics on the one hand, and the widespread ofexclusive interpretation of the Qur’an on the other, integration of Westernhermeneutics to the fild of Qur’anic studies is necessary